COVID-19 Impacts: Empirical Studies on Orion Indoor Sports Business Using Visual Analytics - Bellinda, Suzane (International Journal of Information Technology and Computer Science Applications, 2023)
Covid-19 spreads across the world in just a few months and it has caused severe economic consequences to many countries. Many businesses are also affected dramatically due to the lockdown in order to stop the spread. It does not only affect businesses, it affects how consumers behave in buying and shopping as well. Consumers learn to improvise and get used to the new habits. For example, consumers are not allowed to go to the gyms as they are closed during the lockdown, and they start to work out at home. Technology advances has played a big role in helping the consumers to cope in this situation in an innovative way. Some changes done in an organization to adapt to the pandemic can potentially improve their business tremendously and reduce the losses that already exist before the pandemic. For example, gym equipment sales were only targeting business before the pandemic. However, due to the lockdown, many people were left nowhere to work out and they then prefer to buy gym equipment at home. This will increase the demand of gym equipment and thus boosting the fitness industry business. With the advancement of technology, fitness industry can sell their products online easily and they can also view real-time business performance.